2015
DOI: 10.1162/leon_a_00899
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Culture of Brain Imaging

Abstract: Brain images are believed to be physical explanations for cognitive phenomena. However, the persuasive power of brain imaging cannot be fully explained by the general tendency to biologise the mind in contemporary cognitive sciences. It needs to be understood in relation to histories of imaging techniques, of mediated forms and of their social and cultural discourses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Finally, subdividing neuro-realism into three forms allows for a more in-depth examination into whether and how uncritical reader responses emerge in neuroscience texts. Indeed, considering the three forms and what they do in the text may aid in unraveling the debate about brain images and whether or not they inordinately seduce when framing a neuroscience text containing such rhetorical features (Ali et al, 2014; Farah & Hook, 2013; Gruber & Dickerson, 2012; Hauskin, 2015). Overall, the three forms of neuro-realism tell us more about the varied nature of rhetorical appeals to neuroscience and pave the way for enhanced knowledge about the growing and changing relationship among the neurosciences, the textual structures of the press, and the biosocial configurations offered to and accepted by a public readership.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, subdividing neuro-realism into three forms allows for a more in-depth examination into whether and how uncritical reader responses emerge in neuroscience texts. Indeed, considering the three forms and what they do in the text may aid in unraveling the debate about brain images and whether or not they inordinately seduce when framing a neuroscience text containing such rhetorical features (Ali et al, 2014; Farah & Hook, 2013; Gruber & Dickerson, 2012; Hauskin, 2015). Overall, the three forms of neuro-realism tell us more about the varied nature of rhetorical appeals to neuroscience and pave the way for enhanced knowledge about the growing and changing relationship among the neurosciences, the textual structures of the press, and the biosocial configurations offered to and accepted by a public readership.…”
Section: Resultsmentioning
confidence: 99%
“…Uttal (2011) agrees, claiming that brain images generally entail a “pictorial splendor” that overwhelms critical faculties (p. 21); the loss of “faculties” results in uncritical statements. Hauskin (2015) makes a similar point, suggesting, “Brain images are often presented as pictures providing physical explanations for cognitive phenomena” (p. 68). Yet, the idea that neuro-realist statements derive from the obviousness or seductive nature of brain scan images lacks explanatory power.…”
Section: Background Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Verdi and Kulhavy (2002, 33). Hausken's and Roskies's analyses of fMR images in medical practices show nicely what happens in interpretive processes if people (experts or laypeople) wrongly assume that they are familiar with the results of new imaging technologies (see Hausken 2015;Roskies 2007;. Actually, he mentions three reasons.…”
Section: Personal Conversation With Max Hoffmannmentioning
confidence: 99%
“…These iconic images will remain the essence of visual analysis and the analysis of social reality behind them. A huge amount of work has been done that engages with the use and the analysis of contemporary media-based social practices; they are not branded by the authors as visual sociology but can be identified by visual sociologists as such: see for instance a study on the role of urban surveillance in the night-time economy (Brands et al, 2016), the new aesthetic discourse regarding new media (Sterling, 2012), media aesthetics (Hausken, 2014(Hausken, , 2015 and the social mediapowered shopping practices of transnational Chinese middle-class women (Zhang, 2017), or the materiality of the visual (Bruno, 2014). All these studies focus on the processes directly related to viewing, seeing, recording or otherwise interacting with the visual and in the 'visual sphere' (Nathansohn and Zuev, 2013b) as the context of the ongoing scholarly interrogation.…”
Section: Future Agenda For Visual Sociologistsmentioning
confidence: 99%